Babygate : How to Survive Pregnancy and Parenting in the Workplace - Bakst, Dina; Taubman, Phoebe; Gedmark, Elizabeth (Book collections on Project MUSE., 2014)
An essential guide to navigating the workplace during pregnancy and early parenthood, including a state-specific guide to parents' rights.